REFLECTION OF DOING POST MODERN ETHNOGRAPHIC RESEARCH ON THE DILEMMAS OF WORKING OMANI MOTHERS (Jurnal Kemanusiaan, 2018)
In response to modern ethnography, post-modern ethnography views that reality is multi-faceted and humans are affected and influenced by the research process. This article is a reflection on conducting post-modern ethnographic research on working mothers in Oman. This study is based on my experience doing ethnographic interviews where two different types of interviews were conducted on two groups of research participants. The different modes of interviews yielded variant of outstanding findings which provide comprehensive data useful in providing comprehensive understanding of work-family interface experiences of working Omani women.